2014
DOI: 10.1111/j.1521-0391.2014.12148.x
|View full text |Cite
|
Sign up to set email alerts
|

Quality of life and smoking

Abstract: Understanding the relationship between QoL and tobacco smoking is important for patients, clinicians, and researchers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
101
3
9

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 175 publications
(131 citation statements)
references
References 58 publications
(122 reference statements)
18
101
3
9
Order By: Relevance
“…This finding is also contradictory with the literature [22][23][24][25][26]. Smoking has been repeatedly associated with lower QoL.…”
Section: Discussioncontrasting
confidence: 80%
“…This finding is also contradictory with the literature [22][23][24][25][26]. Smoking has been repeatedly associated with lower QoL.…”
Section: Discussioncontrasting
confidence: 80%
“…Other possible explanations would be indirect, similar to the effect of current smoking on general QOL in conditions related or unrelated to smoking. (2731) Prevalence of affective spectrum disorders in CP patients is high and patients may smoke to relieve anxiety, depression or stress that is pre-existing or develops after diagnosis of CP, or to cope with the need to abstain from drinking. (3235) Smoking cessation by counseling and/or pharmacologic measures should be an important component of the management of CP, not only due to its association with QOL, but also for its impact on disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…It has been pointed out that these self-rated measures of QL may be a marker of poor health (9). It has also been shown that selfperception of "poor" health status has been associated with two-fold higher mortality risk, compared to those who perceive they are in "excellent" health (19).…”
Section: Discussionmentioning
confidence: 99%
“…It has also been shown that selfperception of "poor" health status has been associated with two-fold higher mortality risk, compared to those who perceive they are in "excellent" health (19). In previous studies, QL of smokers has been measured by both generic instruments and smokingspecific scales (9). In our study, we preferred the WHOQL-bref questionnaire, because our study group consisted of healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation